2010
DOI: 10.1590/s0104-59702010000600011
|View full text |Cite
|
Sign up to set email alerts
|

O degenerado

Abstract: Apresenta a emergência da teoria da degenerescência na obra de Benedict-Augustin Morel situando-a no ambiente científico e cultural de sua época e enfatizando o papel das noções de hereditariedade e meio na sua fundamentação e a sua relação com o saber psiquiátrico na medicina mental francesa da metade do século XIX. Analisa os desdobramentos dessa teoria, enfatizando a obra de Valentin Magnan, que culmina na progressiva transição da noção de 'degenerescência' para a de 'degenerado'. Abordam-se os conceitos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…The alienist suggested that the racial mixing of humans from races at different evolutionary stages produced degeneration, that is, a decrease in the resistance of individuals in their biological struggle for life. Therefore, in his view, mixed-raced individuals did not embody a harmonic mixing, but abnormality resulting from the imbalance from joining two bodies at different levels of evolution, leading to the conception of a new life distinguished by unbalancing and differences between these two bodies at levels expressed in their cerebral functions (Magnan & Legrain, 1895;Serpa Jr., 2010). As we can see, Magnan's picture of degeneration was based on new theories and medical referencesneurophysiology and anatomical pathologyand the Morelian metaphysics disappeared, giving room to this new guise.…”
Section: The Degeneration Record As a Historical Referencementioning
confidence: 99%
“…The alienist suggested that the racial mixing of humans from races at different evolutionary stages produced degeneration, that is, a decrease in the resistance of individuals in their biological struggle for life. Therefore, in his view, mixed-raced individuals did not embody a harmonic mixing, but abnormality resulting from the imbalance from joining two bodies at different levels of evolution, leading to the conception of a new life distinguished by unbalancing and differences between these two bodies at levels expressed in their cerebral functions (Magnan & Legrain, 1895;Serpa Jr., 2010). As we can see, Magnan's picture of degeneration was based on new theories and medical referencesneurophysiology and anatomical pathologyand the Morelian metaphysics disappeared, giving room to this new guise.…”
Section: The Degeneration Record As a Historical Referencementioning
confidence: 99%
“…The concept of “degeneracy”, inaugurated by the European theorist Morel, represented “a deviation from the ideal type”, “the degradation of Customs“, “the gradual and progressive decay of a perfect primitive type” 12 . Degeneracies and deviations were seen as products of heredity and social disorder 13 .…”
Section: Introductionmentioning
confidence: 99%
“…O conceito de “degenerescência”, inaugurado pelo teórico europeu Morel, representava “um desvio do tipo ideal”, “a degradação dos costumes”, “a decadência gradual e progressiva de um tipo primitivo perfeito” 12 . As degenerescências e desvios foram vistos como produtos da hereditariedade e da desordem social 13 .…”
Section: Introductionunclassified
“…No caso de Magnan, vale ainda destacar outra característica definidora da condição do degenerado. Trata-se do 'desequilíbrio' (Serpa Jr., 2010). Partindo da concepção poligenista da origem das raças 10 (e, nesse sentido, opondo-se à perspectiva monogenista moreliana),…”
unclassified